Financial situation of pre-packed insolvencies - Schönfeld, Jaroslav (Journal of Business Economics and Management, 2020)
This paper is focused on the financial situation of companies entering insolvency proceedings. It does not work with all kinds of the insolvent companies, but this paper concentrates on one specific issue. The issue is pre-pack insolvencies. The main aim is to show if the financial situation is an important factor for consent to pre-pack. The pre-pack insolvencies are insolvency cases which start with an insolvency proposal which is accompanied by a reorganization plan already approved by creditors. Prepacks should help make the insolvency process quicker and enable enterprise financial rehabilitation and sustain the going concern principle. On the other hand, the procedure can hardly be successful when the financial situation of the company is extremely poor. Therefore this paper evaluates the financial situation of the companies with pre-packed insolvency in the Czech Republic. The analysis of companies was conducted over one, two or three year periods prior to the companies entering an insolvency proceeding. According to the literature, financial indicators used for evaluation are commonly EBITDA, cash liquidity, debt ratio, ROA and the Altman Z-Score prediction model. Results for the individual enterprises are summed up in this paper using basic descriptive and variable statistics. Conclusions have especially practical implications because they show financial inability of majority pre-packed cases.